An Analysis of the Risk Factors for Adding-on Phenomena After Posterior Hemivertebral Resection and Pedicle Screw Fixation for the Treatment of Congenital Scoliosis Caused by Hemivertebral Malformation - Bao BX; Yan H; Tang JG; Qiu DJ; Wu YX; Cheng XK (Dove Medical Press, 2022)
Bei-Xi Bao, Hui Yan, Jia-Guang Tang, Dao-Jing Qiu, Yu-Xuan Wu, Xiao-Kang Cheng Department of Orthopedic Surgery, Beijing Tongren Hospital, Capital Medical University, Beijing, 100730, People's Republic of ChinaCorrespondence: Jia-Guang Tang, Department of Orthopedic Surgery, Beijing Tongren Hospital, Capital Medical University, No. 1 of Dongjiaominxiang Street, Dongcheng District, Beijing, 100730, People's Republic of China, Tel/Fax +86 13911003227, Email jgtang123@163.comObjective: To retrospectively analyze the risk factors for adding-on phenomena (AOP) after posterior hemivertebral resection (PHR) and pedicle screw fixation for the treatment of congenital scoliosis (CS) caused by hemivertebral (HV) malformation.Methods: Patients with CS who underwent surgery and were followed up for more than five years were included in this study. The d general data, such as gender, age, HV segment, Risser sign, and triangular cartilage, postoperative complications, and imaging data at different periods, including the standard anteroposterior and lateral x-rays of the total spine were collected.Results: In total, 58 patients were included in this study, of which 10 experienced AOP and 48 did not. The results of the single-factor analysis showed that there were statistically significant differences between the patients with AOP and those without in terms of the HV direction, lowest instrumented vertebra (LIV)-upper instrumented vertebra (UIV) (P < 0.05), and postoperative trunk shift (P < 0.05). The results of the logistic regression analysis showed that the HV direction and the postoperative trunk displacement distance were the main risk factors for postoperative AOP. The area under the receiver operating characteristic curve was 0.842 (P < 0.001). The best cut-off value of the adding-on index as an indicator of the occurrence of AOP after surgery was 0.67. When the adding-on index was > 0.67, the incidence of postoperative AOP was 90.0%, and the non-occurrence rate was 22.9%.Conclusion: PHR and pedicle screw fixation is an effective way to treat HV malformation in CS. The HV direction, LIV-UIV, and postoperative TS are risk factors for AOP in patients with CS treated with PHR and pedicle screw fixation. The adding-on index has a high degree of accuracy for the prediction of the occurrence of AOP after PHR and pedicle screw fixation.Keywords: congenital scoliosis, hemivertebral resection, adding-on phenomena